2004
DOI: 10.1016/j.jtcvs.2003.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with atrial fibrillation after noncardiac thoracic surgery: analysis of 2588 patients

Abstract: The significant variables identified by means of multivariate analysis were associated with the occurrence of atrial fibrillation. Preventive therapies in selected populations might reduce the incidence of atrial fibrillation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
212
4
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 321 publications
(237 citation statements)
references
References 29 publications
18
212
4
3
Order By: Relevance
“…In previous reports, advanced age has been described as the most significant predictor of newonset AF after CABG. [23][24][25] Aging leads to structural changes in heart such as atrial fibrosis, scarring, and dilatation. [26] Increased sympathetic activation and prolonged atrial conduction time by aging are likely responsible for PoAF development.…”
Section: Discussionmentioning
confidence: 99%
“…In previous reports, advanced age has been described as the most significant predictor of newonset AF after CABG. [23][24][25] Aging leads to structural changes in heart such as atrial fibrosis, scarring, and dilatation. [26] Increased sympathetic activation and prolonged atrial conduction time by aging are likely responsible for PoAF development.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperatif atriyal fibrilasyonda izlenecek yol [11] . [21][22][23][24] . Akciğer rezeksiyonundan sonra AF oluşumunu önlemek için amiodarone, MgSO 4 , digoksin, ve Ca2…”
Section: Postoperatif Gün +5unclassified
“…It has been reported that its occurrence, including atrial fibrillation (AF) and paroxysmal supraventricular tachycardia (PSVT), increases postoperative complications and mortality rates [3][4][5][6][7][8][9][10]. Postoperative tachyarrhythmia is associated with delayed early mobilization, prolonged postoperative hospital stay, and increased medical costs of open thoracic operations [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Although patient selection and improved postoperative care can significantly decrease hospital mortality rates, the morbidity rate remains high [11][12][13][14][15][16]. Tachyarrhythmia is among the most frequent complications of esophagectomy [10,[12][13][14]. Atrial fibrillation after esophagectomy was reported to be a marker for postoperative morbidity and mortality [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%